Sport sciences contribution in Olympic preparation and performance: updating italian experience - Faina, M.; Broccardo, D.; Dalla Vedova, D.; de Angelis, M.; Gianfelici, A. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
A sport performance relies on several factors that could be summarized by the ratio between the power expressed by the athlete and the Energy Cost (EC) of movement. Among the factors that contribute to improve the athlete`s capability of expressing power, both mechanic or metabolic, there should be mentioned: the improvement of the physiological qualities, the stress management, a correct dietary supplementation, etc. The reduction of EC of a locomotion depends on a correct neuro-muscular specific coordination, on an optimal technique on driving the mean of competition, on the utilisation of up-to-dated materials, etc. So, when it`s referred to the technical-scientific support for improving the preparation or/and the performance, they are normally intended all the information or methodologies or methods or devices that could help coaches to optimize one or more of the indicated factors, by a specific training program. The Italian National Olympic Committee, referring to these principles, since 2002 has established a special project, named "Torino 2006", aimed to support the Winter Sports Federations, whenever they had wanted, in their way towards the Olympic Games of Torino 2006. The Institute of Sport Science has been directly involved in that project and, with other Institutions, mostly Universities, it works with some of the sport disciplines involved in the next Olympic Games studying the different aspects related with the sport performance. Main attention has been paid both on the physiological factors (e.g. the definition of physiological responses in competitive conditions or monitoring of training effects, etc.) and on the biomechanical factors, like the relations between the athlete and the mean of competition. As examples of measurements carried out on physiological field, there should be mentioned the analysis on crosscountry skiing to define: 1) the functional responses in short races; 2) the optimal warm-up before short races; 3) the reliability of anaerobic threshold parameters, when they are detected in lab or on field. As far as the studies carried out on biomechanical filed are concerned, there could be quoted: 1) the evaluation of skating blade friction; 2) the recording and evaluation of bob, luge and skeleton driving technique; 3) the study of the kinematics of pushing phase of the above mentioned disciplines as well as of the cross country skiing. At the aim of giving a clearer comprehension of the support given by Sport Sciences to the preparation of the Olympic teams, it`s shown the work methodology and the monitoring of some metabolic parameters of the National speed skating team during several seasons. Similarly, it`s shown the biomechanical analysis during the starting phase of the single male Olympic luge. Force expressed by the athlete have been detected by applying strain gauges on the handlebars (in cooperation with the Engineering Faculty of the Padoa University), evaluating the quantitative aspects as well as the occasional asymmetry between the right and left arm in the pushing action. The integration with a video-analysis system gives a more detailed evaluation of the technical movement.